Status of memory loss. (18th April 2012) - Iyer, Parameswaran Mahadeva; Moroney, Joan; Mullins, Gerard; Farrell, Michael; Delanty, Norman
Abstract : A 72-year-old woman presented with first onset of seizure with no prior history of cognitive dysfunction. EEG revealed focal non-convulsive status epilepticus. MRI brain showed a left temporal non-enhancing lesion. Temporal pole biopsy showed acute neuronal necrosis and astrocyte hyperplasia together with extensive amyloid plaques and neurofibrillary tangles. Perivascular oligodendroglial hyperplasia was present. Postmortem examination revealed extensive plaque and tangle disease. Perivascular oligodendroglial hyperplasia was limited to the left temporal area. The presence of focal perivascular oligodendroglial hyperplasia in the left temporal cortex, combined with extensive plaque and tangle disease may have contributed to the focal status epilepticus in this patient. Although the presence of focal perivascular oligodendroglial hyperplasia has been reported in cases of temporal lobe epilepsy, it has not been reported as a cause of seizure in patients with Alzheimer's disease previously. Further studies for clinical-pathologic correlation would be required to confirm this hypothesis.